Catalyst Design by NH4OH Treatment of USY Zeolite. (30th October 2015) - Van Aelst, Joost; Verboekend, Danny; Philippaerts, An; Nuttens, Nicolas; Kurttepeli, Mert; Gobechiya, Elena; Haouas, Mohamed; Sree, Sreeprasanth P.; Denayer, Joeri F. M.; Martens, Johan A.; Kirschhock, Christine E. A.; Taulelle, Francis; et al.
Abstract : Hierarchical zeolites are a class of superior catalysts which couples the intrinsic zeolitic properties to enhanced accessibility and intracrystalline mass transport to and from the active sites. The design of hierarchical USY (Ultra‐Stable Y) catalysts is achieved using a sustainable postsynthetic room temperature treatment with mildly alkaline NH4 OH (0.02m ) solutions. Starting from a commercial dealuminated USY zeolite (Si/Al = 47), a hierarchical material is obtained by selective and tuneable creation of interconnected and accessible small mesopores (2–6 nm). In addition, the treatment immediately yields the NH4 + form without the need for additional ion exchange. After NH4 OH modification, the crystal morphology is retained, whereas the microporosity and relative crystallinity are decreased. The gradual formation of dense amorphous phases throughout the crystal without significant framework atom leaching rationalizes the very high material yields (>90%). The superior catalytic performance of the developed hierarchical zeolites is demonstrated in the acid‐catalyzed isomerization of α‐pinene and the metal‐catalyzed conjugation of safflower oil. Significant improvements in activity and selectivity are attained, as well as a lowered susceptibility to deactivation. The catalytic performance is intimately related to the introduced mesopores, hence enhanced mass transport capacity, and the retained intrinsic zeolitic properties. Abstract : Postsynthetic NH4 OH treatment is performed on USY (ultra‐stable Y) zeolite to sustainably develop superior catalysts. Extensive characterization shows the selective creation of small mesopores by partial zeolite densification without significant material leaching. The hierarchical zeolite outperforms the conventional USY for acid‐catalyzed isomerization of α‐pinene and metal‐catalyzed conjugation of safflower oil, which is attributed to its enhanced intracrystalline mass transport capacity.